New Mediterranean Marine biodiversity records (April, 2014) - Kapiris, K.; Apostolidis, C.; Baldacconi, R.; Basusta, N.; Bilecenoglu, M.; Bitar, G.; Tiralongo, F. (Natl Centre Marine Research, 2014)
According to reports, the following 16 species have extended their distribution to other Mediterranean areas or have made a new appearance in other regions. The first category includes the following organisms: The rare and common Indo-Pacific seaweed Codium arabicum (Lebanese coasts), the acari Thalassarachna affinis (Marmara Sea), and the non-indigenous nudibranch Flabellina rubrolineata, which has been found in several areas of the Aegean Sea. In addition, the rare sea slug Thecacera pennigera (Mar Piccolo of Taranto), the fangtooth moray Enchelycore anatina (National Marine Park of Zakynthos, Ionian Sea), the carangid Seriola fasciata (Gulf of Antalya), Lagocephalus sceleratus (SE Ionian Sea), the reticulated leatherjacket Stephanolepis diaspros (Slovenia, N. Adriatic Sea), the marbled stingray, Dasyatis marmorata (NE Levantine), the starry smooth-hound Mustelus asterias (Iskenderun Bay, NE Mediterranean), the cephalopod Ommastrephes bartramii (Ionian Sea) have also been reported. The Atlantic crab Dyspanopeus sayi has expanded to many Italian areas and the blue crab Callinectes sapidus to a lake in N. Greece and in the S. Adriatic Sea. Finally, Farfantepenaeus aztecus has been found in the Ionian Sea, thus showing its wide expansion in the Mediterranean. The larval stages of Faccionella oxyrhyncha have been found, after many years, in the Aegean Sea and the first report of an existence on intersexual acari Litarachna duboscqi in Split (Adriatic Sea) was reported.
Keywords: Ommastrephes-Bartramii Cephalopoda; Lagocephalus-Sceleratus Gmelin; Callinectes-Sapidus Rathbun; Moray Enchelycore-Anatina; 1St Record; Mud Crab; Facciolas Sorcerer; Indo-Pacific; Blue-Crab; Sea